The clinical effectiveness assessment of proposed digital dental planning and digital smile prototypes design - Jameel, Rawan M; Stanislavovich, Lesovik V (Journal of Baghdad College of Dentistry, 2025)
Background: Modern technologies in dentistry are one of ‎the effective ‏methods to obtain ‎results that are acceptable to the ‎‎patient, as well as reducing time, ‏effort, and ‏‎‎cost. ‏Materials and Methods: The effectiveness of the developed ‎digital ‎dental ‎treatment ‎‎‏planning was evaluated by assessing the results of ‎a survey of 50 ‎patients in need of ‎‎‎dental ‏‎implant prosthesis for aesthetic ‎‏faults ‎‎‎of the anterior tееth at the ‏prototype stage. The Oral ‏‎‎Health ‏Impact ‏Profile-14 (OHIP-14) was created to measure ‎the ‏impact that ‏oral health ‎issues can have on a person’s life. ‎‎Results: after the mockup the ‏relative occlusal load distribution ‏‎between the right and left sides was 50.40 ± 0.90% with ‏balanced ‏‎occlusion.‏The dental closing time was 0.17± 0.07 s; and the dental ‎opening time ‏was 0.19 ±0.04 s. The difference in timing between the ‎left and right latеrntrusions is -0.030 ‎‎± 0.03. During protrusion, the ‎‎opening time was less than 0.6 s. (0.170 ± 0.07).‎‎ ‎‎ The ‏time ‎required to close the teeth to reach the maximum intercuspation was 0.20 ± 0.02 s, where the time required to open them was ‎‎0.170 ± 0.02 s. Conclusion: Prior to the mock-up, the patients’ average relative occlusal load distribution was 51.5±1.20% on the left and right sides. After the mock-up, it was found that the relative occlusal load distribution between the left and right sides was 50.40±0.90%. These results point to stable and successful occlusal balance restoration following mock-up. After using the OHIP-14 questionnaire to summarize the survey results, we can say that patients’ quality of life has enhanced by a factor of two.